Association of Self-Reported Quality of Life in Children with Level of Bronchial Asthma Control - Shalini Verma; Shally Awasthi; Sarika Gupta (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: To assess the association of self-reported quality of life (QOL) by using mini- pediatric asthma quality of life questionnaire (mini-PAQLQ) in children aged between 7-15 years with a level of asthma control. Subjects and Methods: Prospective observational study conducted in the asthma clinic in the outpatient department from September 2016 to August 2017. All the cases of asthma, as defined by GINA guidelines, aged between 7-15 years with parental consent were recruited. The level of control was also assessed according to GINA guidelines. Excluded were clinically suspected cases of chronic lung diseases except for bronchial asthma and any other chronic medical condition. QOL was assessed by using mini-PAQLQ which had three domains i.e. Symptoms, emotions and limitation of activity. Each domain had questions and their responses coded on a visual scale with 7 options. Results: From September 2016 to August 2017, total enrolled were 85 of which 51 (60%) were partly controlled and 34(40%) were well controlled. Mean mini-PAQOL score in patients with partly control was low (3.59 0.93) as compared to those with well-controlled asthma (5.83 1.21) (p=0.0001). Conclusion: Self-reported QOL of children with partly controlled asthma was found to be impaired in all the domains as compared to those with well-controlled asthma.